1997
DOI: 10.1002/(sici)1098-2795(199710)48:2<292::aid-mrd18>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase C is required for the disappearance of MPF upon artificial activation in mouse eggs

Abstract: The aim of the present study was to investigate the implication of protein kinase C (PKC) in the mouse egg activation process. We used OAG (1‐oleoyl‐2‐acetyl‐sn‐glycerol) as a PKC activator, calphostin C as a specific PKC inhibitor, and the calcium ionophore A23187 as a standard parthenogenetic agent. The exposure of zona‐free eggs to 150 μM or 50 μM OAG for 10 min resulted in meiosis II completion in ∼80% of instances. By contrast, at a lower concentration (25 μM), the PKC stimulator was ineffective as parthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(4 citation statements)
references
References 41 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…PKC Q was also detected by immunohistochemistry (data not shown). The presence of many PKC isozymes in the egg, including PKC Q, as already demonstrated in Xenopus [17], is not surprising, since the egg is a totipotential cell which may contain various PKC isozymes involved in di¡erent developmental processes. However, since PKC Q is known to be brain-speci¢c in the adult, its role in this early stage of development should be further elaborated.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…PKC Q was also detected by immunohistochemistry (data not shown). The presence of many PKC isozymes in the egg, including PKC Q, as already demonstrated in Xenopus [17], is not surprising, since the egg is a totipotential cell which may contain various PKC isozymes involved in di¡erent developmental processes. However, since PKC Q is known to be brain-speci¢c in the adult, its role in this early stage of development should be further elaborated.…”
Section: Resultsmentioning
confidence: 67%
“…However, PKC inhibitors failed to block fertilization‐induced cortical reaction [13]. Other studies demonstrated cell cycle resumption in eggs treated with PKC [14–17]. Very few studies have actually analyzed the presence of different PKC isozymes and their biological activity in eggs.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that PKC is involved in cell cycle resumption and progression during oocyte activation. PKC pharmacological inhibitors or activators respectively blocked or induced meiotic resumption MII oocyte (Colonna et al, 1997; Eliyahu & Shalgi, 2002; Gallicano et al, 1997; Gallicano, Schwarz, McGaughey, & Capco, 1993). However, in the present work, PKC inhibition with 10 µM BIM was not enough to suppress meiotic resumption after bovine oocyte parthenogenetic activation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus PKC activity rises during egg activation when measured directly (Gallicano et al, 1997a), or indirectly by redistribution of various isoforms to the plasma membrane (Eliyahu and Shalgi, 2002;Luria et al, 2000). Furthermore inhibitors of PKC have been reported to prevent mammalian eggs exiting MetII arrest (Gallicano et al, 1997a), and conversely PKC activators are reported to induce completion of meiosis (Colonna et al, 1997;Gallicano et al, 1993;Luria et al, 2000).…”
Section: Introductionmentioning
confidence: 98%